Research evidence. Issue 7 (2nd July 2021) - Leitch, Neil
Abstract : Neil Leitch, chief executive of the Early Years Alliance, outlines findings from its provider survey on the pandemic's impact and the challenges the sector faces in tackling the disadvantage gap in pre-schoolers